2010
DOI: 10.3109/03639040903170750
|View full text |Cite
|
Sign up to set email alerts
|

The application of mucoadhesive polymers in nasal drug delivery

Abstract: The mucoadhesive polymers have enormous potential for the delivery of therapeutic macromolecules, genes, and vaccines through the nasal cavity with high drug bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 122 publications
0
26
0
3
Order By: Relevance
“…Использование в качестве регуляторов вязкости мукоадгезивных полимеров, таких как полиакриловая кислота, карбомер, хитозан, альгинат натрия, метилцеллюлаза, гидроксипропилметилцеллюлоза, карбоксиметилцеллюлоза, повышает комфортность их применения, позволяет увеличивать время контакта лекарственного препарата со слизистой оболочкой полости носа и приводит к увеличению абсорбции лекарственного вещества [49]. Некоторые из этих веществ относятся к так называемым умным («smart») полимерам.…”
Section: регуляторы вязкостиunclassified
“…Использование в качестве регуляторов вязкости мукоадгезивных полимеров, таких как полиакриловая кислота, карбомер, хитозан, альгинат натрия, метилцеллюлаза, гидроксипропилметилцеллюлоза, карбоксиметилцеллюлоза, повышает комфортность их применения, позволяет увеличивать время контакта лекарственного препарата со слизистой оболочкой полости носа и приводит к увеличению абсорбции лекарственного вещества [49]. Некоторые из этих веществ относятся к так называемым умным («smart») полимерам.…”
Section: регуляторы вязкостиunclassified
“…Drugs administered intranasally in the form of solutions are usually cleared rapidly (within around 15 min) by mucociliary clearance mechanism from the nasal cavity towards the nasopharyngeal region (Mao et al, 2004). Mucoadhesive agents, also referred to as bioadhesive agents, have been investigated with the aim of enhancing drug absorption across the epithelial cells of the nose (Jiang et al, 2010;Salade et al, 2018). Incorporation of drugs into mucoadhesive delivery systems is a highly promising strategy for enhancing drug absorption through the nasal epithelium.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[34,111,112,113,114,115] Araújo et al , (2014) [115] have demonstrated that in chitosan coated nanocarriers (e.g., poly(lactide- co -glycolide), solid lipid nanoparticles and porous silicon), a more sustained release of payload (e.g., glucagon like peptide-1) with enhanced bioavailability resulted from its mucoadherent tendency. Thus, these DDS can be utilized in ocular [116,117,118,119], buccal [120,121,122,123], nasal [124,125,126,127], pulmonary [128,129,130,131], vaginal [132,133,134,135,136], or rectal [137,138,139,140] delivery, for eliciting a therapeutic effect either locally or systemically [13,114,141].…”
Section: Critical Role Of Mucin Network In Impacting Diverse Bioapmentioning
confidence: 99%